Microvascular resistance in response to iodinated contrast media in normal and functionally impaired kidneys. (December 2015) - Kurihara, Osamu; Takano, Masamichi; Uchiyama, Saori; Fukuizumi, Isamu; Shimura, Tetsuro; Matsushita, Masato; Komiyama, Hidenori; Inami, Toru; Murakami, Daisuke; Munakata, Ryo; Ohba, Takayoshi; Hata, Noritake; et al.
Summary: Contrast‐induced nephropathy (CIN) is considered to result from intrarenal vasoconstriction, and occurs more frequently in impaired than in normal kidneys. It was hypothesized that iodinated contrast media would markedly change renal blood flow and vascular resistance in functionally impaired kidneys. Thirty‐six patients were enrolled (32 men; mean age, 75.3 ± 7.6 years) undergoing diagnostic coronary angiography and were divided into two groups based on the presence of chronic kidney disease (CKD), defined as an estimated glomerular filtration rate (eGFR) of < 60 mL/min per 1.73 m 2 (CKD and non‐CKD groups, n = 18 in both). Average peak velocity (APV) and renal artery resistance index (RI) were measured by Doppler flow wire before and after administration of the iodinated contrast media. The APV and the RI were positively and inversely correlated with the eGFR at baseline, respectively (APV, R = 0.545, P = 0.001; RI, R = −0.627, P < 0.001). Mean RI was significantly higher ( P = 0.015) and APV was significantly lower ( P = 0.026) in the CKD than in the non‐CKD group. Both APV ( P < 0.001) and RI ( P = 0.002) were significantly changed following contrast media administration in the non‐CKD group, but not in the CKD group (APV, P = 0.258; RI, P = 0.707). Although renal arterial resistance was higher in patients with CKD, it was not affected by contrast media administration, suggesting that patients with CKD could have an attenuated response to contrast media.